2017
DOI: 10.1063/1.4974831
|View full text |Cite
|
Sign up to set email alerts
|

Liquid dynamics in partially crystalline glycerol

Abstract: We present a dielectric study on the dynamics of supercooled glycerol during crystallization. We explore the transformation into a solid phase in real time by monitoring the temporal evolution of the amplitude of the dielectric signal. Neither the initial nucleation or the crystal growth influence the liquid dynamics visibly. For one of the samples studied, a tiny fraction of glycerol remained in the disordered state after the end of the transition. We examined the nature of the α relaxation in this frustrated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 45 publications
3
14
3
Order By: Relevance
“…As can be seen, the values of Δε (amplitude of α-peak) slightly increase with time. In this context, it is worthwhile to mention the studies on glycerol carried out by Sanz and Niss . The authors observed that, in contrast to our data, the dielectric permittivity (which is related to the dielectric strength of α-process) decreases with the time during annealing.…”
Section: Results and Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…As can be seen, the values of Δε (amplitude of α-peak) slightly increase with time. In this context, it is worthwhile to mention the studies on glycerol carried out by Sanz and Niss . The authors observed that, in contrast to our data, the dielectric permittivity (which is related to the dielectric strength of α-process) decreases with the time during annealing.…”
Section: Results and Discussioncontrasting
confidence: 83%
“…In this context, it is worthwhile to mention the studies on glycerol carried out by Sanz and Niss. 56 The authors observed that, in contrast to our data, the dielectric permittivity (which is related to the dielectric strength of α-process) decreases with the time during annealing. This effect was related to the nucleation phenomenon.…”
contrasting
confidence: 99%
“…The failure of a fraction of the EAM sample to crystallize is reminiscent of the behavior of other H-bonded liquids. In the case of glycerol, a sample recrystallized from the supercooled liquid state was reported to undergo incomplete crystallization with a final amorphous fraction of about 1%, 64 a value smaller than that obtained here for EAM. An extreme example is that of n-butanol, where the amorphous fraction at the end of the crystallization process is reported to be as high as 20 or 30%, 65 although the origin of this effect is likely different than for EAM.…”
Section: Electric Conductivity and Dielectric Relaxations In Eamcontrasting
confidence: 81%
“…An extreme example is that of n-butanol, where the amorphous fraction at the end of the crystallization process is reported to be as high as 20 or 30%, 65 although the origin of this effect is likely different than for EAM. The relatively low value of the amorphous fraction in EAM (this study) and glycerol 64 suggests that the amorphous regions are limited in both cases to the boundaries of crystallites that occupy almost the totality of the sample's volume. As mentioned above, in addition to the BNN and  relaxations a third, weak relaxation feature () is present at lower temperature ( Figure 6(a,c)), where the amorphous EAM fraction is close to the glass transition.…”
Section: Electric Conductivity and Dielectric Relaxations In Eammentioning
confidence: 60%
“…This phenomenological relation reads as follows: where τ 0 is a pre-exponential factor with phonon-like time scales, D is a strength parameter related to the dynamic fragility and T 0 is the Vogel temperature (divergence at T = T 0 ) ( Vogel, 1921 ; Fulcher, 1925 ; Tammann, 1925 ). The VFT equation is a powerful tool for interpolating experimental points and quantifying the steepness of the α relaxation plot ( Ediger et al, 1996 ; Sanz and Niss, 2017 ). For the segmental dynamics (◦), the solid lines in Figure 7 correspond to VFT fits.…”
Section: Resultsmentioning
confidence: 99%